2020
DOI: 10.1186/s13005-020-00236-0
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of type p condylar head osteosynthesis using conventional small-fragment screws reinforced by a patient specific two-component plate

Abstract: Background The aim of this study was to evaluate via finite element analysis (FEA) the biomechanical behavior of conventional small-fragment screws reinforced by a patient-specific plate in type p condylar head. Methods A finite element model of the mandible was created using Mimics 12.1 software. A type p condylar head fracture was simulated in the right condyle, and the left condyle was used as a control. Two patterns of fixation were investigated: conventional two-screw fixation and the same fixation syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…However, it is not the only option, especially in multifracture fractures. A new approach from the Kiev team [5,6] with custom-made plates for proximal fragment reduction is a very interesting solution to a serious clinical issue. Consideration could be given to manufacturing these customized plates with magnesium alloy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not the only option, especially in multifracture fractures. A new approach from the Kiev team [5,6] with custom-made plates for proximal fragment reduction is a very interesting solution to a serious clinical issue. Consideration could be given to manufacturing these customized plates with magnesium alloy.…”
Section: Discussionmentioning
confidence: 99%
“…Titanium alloys are used in skeletal surgery, in both children [1][2][3] and adults [4][5][6][7]. Long screw fixation through the lateral fragment end of the ascending ramus (i.e., distal fragment) has been a well-known procedure for osteosynthesis of the condylar head for approximately the last 30 years [8].…”
Section: Introductionmentioning
confidence: 99%
“…This results in excellent final results. In the condylar head region, custom repositioning plates/mesh according to the Ukrainian concept is a highly promising prospect [ 76 , 77 ]. Full adaptation to the details of the mandibular head anatomy can be cited as specific applications [ 78 ] to induce faster cell growth, more cell divisions, and eventually better quality bone consolidation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 31 ] Relatively high survival rate of PSI in our study with a long-term follow-up compared to the results reported for the mandible with PSI failure from 12.5% to 27% could be explained by the influence of predominantly static bio-mechanical loading of the implants with low stress and strains values. [ 32 33 ] However, excessive tension of skin above the implant can be considered as risk factor of its exposure and should be prevented during at CAD stage of the treatment planning. [ 1 7 25 ]…”
Section: Onclusionmentioning
confidence: 99%